The devil at his elbow: Alex Murdaugh and the fall of a southern dynasty - Bauerlein, Valerie (Ballantine Books, 2024)
"Power, privilege, and blood-this is the definitive and thrilling true story of Alex Murdaugh's violent downfall, from a veteran Wall Street Journal reporter who has become an authority on the case"--